Evaluation of the effect of water action on the physical and mechanical properties of asphalt mixtures from the Amazon region under conditions of induced moisture - Salgado Barra, Breno (2025)
Being water one of the most detrimental natural agents affecting the maintenance of the physical and mechanical properties of pavements throughout their service life, the main focus of this study is to address the effect of water action on asphalt mixtures under conditions of induced moisture, using the theoretical principles proposed in the Modified Lottman Test (AASHTO T-283/89). The Amazon region, and particularly the State of Pará, was selected for material sourcing due to its high annual rainfall levels, ranging from approximately 2500 mm to 3000 mm. This high precipitation influenced the choice of materials used to formulate the mineral skeleton of the asphalt mixtures (senior granite aggregate, quartz sand, and limestone powder). The petroleum asphalt cement used (CAP 50/70) was sourced from the Lubricants and Petroleum Derivatives Refinery of the Northeast, located in the State of Ceará (LUBNOR/CE). A comparative analysis was conducted between asphalt mixtures produced using gradation curves formulated through the Fuller or Talbot Equation (referred to as theoretical curves) and those used in Brazil, such as the gradation curves from the National Department of Transport Infrastructure (DNIT). The DNIT Curve C was specifically explored, as it is widely used in the region for paving services.The study demonstrates the damaging effect of water in asphalt mixtures when present in the interstices of their composition, particularly under conditions of high thermal gradient.